2021
DOI: 10.1097/ijg.0000000000001834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Nerve Fiber Layer, Ganglion Cell-Inner Plexiform Layer, and Optic Nerve Head in Glaucoma Suspects With Varying Myopia

Abstract: Précis: Myopic glaucoma suspects, particularly with high myopia, experience thinning of nontemporal parameters of retinal nerve fiber layer (RNFL) and ganglion cell-inner plexiform layer (GCIPL), without change in optic nerve head (ONH) parameters. Purpose:The aim was to assess the effect of myopia on RNFL, GCIPL, and ONH parameters in glaucoma suspects.Materials and Methods: Seventy-six eyes of glaucoma suspects studied with Cirrus high definition optical coherence tomography were divided into low (n = 27), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…In addition we found that peripapillary RNFL thickness in the T quadrant was significantly higher in patients with high myopia when compared with OAG and OAG-M groups. This corresponds with other studies’ results that observed thickening of RNFL in the T quadrant in high myopia due to the temporalization of RNFL due to increased AL [ 25 , 42 44 ]. The RNFL thickness in the T quadrant is expected to be the least affected by high myopia changes suggesting that a decrease in RNFL thickness in this part could indicate glaucomatous changes [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition we found that peripapillary RNFL thickness in the T quadrant was significantly higher in patients with high myopia when compared with OAG and OAG-M groups. This corresponds with other studies’ results that observed thickening of RNFL in the T quadrant in high myopia due to the temporalization of RNFL due to increased AL [ 25 , 42 44 ]. The RNFL thickness in the T quadrant is expected to be the least affected by high myopia changes suggesting that a decrease in RNFL thickness in this part could indicate glaucomatous changes [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…This corresponds with other studies’ results that observed thickening of RNFL in the T quadrant in high myopia due to the temporalization of RNFL due to increased AL [ 25 , 42 44 ]. The RNFL thickness in the T quadrant is expected to be the least affected by high myopia changes suggesting that a decrease in RNFL thickness in this part could indicate glaucomatous changes [ 44 ]. Previously, Tai and colleagues found that mean and I quadrant RNFL thickness was lower in high myopia than in OAG patients [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…Studies ( 31 , 32 ) demonstrated that GCIPL thicknesses were significantly thinner with decreasing SE and also significantly thinner with increasing axial length. Miller et al ( 13 ) found patient with high myopia experience thinning of non-temporal parameters ganglion cell-inner plexiform layer. Our study displayed similar results that both myopia and GP could lead to a decrease in the average and sectoral GCIPL, but the annual change rate of inferotemporal GCIPL in the GP group was much greater than that in the MP group.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identifying the difference in the loss pattern of the pRNFL and RGCs caused by glaucomatous or myopic progression in adolescents is critical for the early detection of juvenile glaucoma. To date, most studies ( 6 , 13 ) that have compared the pRNFL and RGCs between myopia and glaucoma were cross-sectional investigations on adults, which limits the insights that can be drawn from the data regarding the time course of pRNFL and RGCs changes associated with the progressive myopia and glaucoma during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…RNFL thinning has been previously reported in patients with OSA, along with decreased visual evoked potentials [ 9 , 10 , 31 47 , 56 ]. Importantly, while RNFL thinning has been reported in myopic eyes and associated with health conditions including migraines, diabetes, multiple sclerosis, Parkinson’s disease, and Alzheimer’s disease, this usually results in more diffuse thinning [ 57 62 ]. In contrast, the pattern of thinning shown in this study is consistent with glaucomatous changes that follow an ISNT (inferior, superior, nasal, and then temporal) pattern.…”
Section: Discussionmentioning
confidence: 99%